2010
DOI: 10.1167/iovs.09-4215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Increase in Blood Pressure on Intraocular Pressure in Pigs and Humans

Abstract: The pharmacological approach in animals and the study of isometric exercise in humans show that IOP rises significantly and rapidly with kinetics close to those of BP, and the two values are linearly related. The absence of variation in capnia and the greater increase in BP during squatting may explain the greater increase in IOP during this exercise compared to handgripping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…While a significant change in IOP was observed during the course of isometric exercise, this change dissipated rapidly following completion. These findings are in line with previous studies that observed a significant increase in IOP during isometric exercise, which decreased back to baseline [22][23] or even below baseline within a minute following the exercise [14][15][16][17][18][19]. Movaffafhy et al [14] and Riva et al [15] observed that an increase in blood volume within the large choroidal vessels could explain the increase in IOP during squatting.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While a significant change in IOP was observed during the course of isometric exercise, this change dissipated rapidly following completion. These findings are in line with previous studies that observed a significant increase in IOP during isometric exercise, which decreased back to baseline [22][23] or even below baseline within a minute following the exercise [14][15][16][17][18][19]. Movaffafhy et al [14] and Riva et al [15] observed that an increase in blood volume within the large choroidal vessels could explain the increase in IOP during squatting.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of exercise on IOP has been well studied [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Although the majority of studies agree that dynamic exercise produces a decrease in IOP [8][9][10][11][12][13], no consensus was found for the effect of isometric exercise (i.e., static strength training where the joint angle and muscle length do not change during the contraction).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in systemic blood pressure have been shown to correlate with changes in IOP in humans and pigs. 10 Endocrinology studies in avian species have confirmed that, as in mammals, short-term stress in birds results in release of corticosterone and catecholamines from the adrenal gland. Of the many effects of these hormones, increase in systemic blood pressure is one of the most significant.…”
Section: Species (P) a Study In Black-footed Penguins Reported Iop Mmentioning
confidence: 91%
“…27 This is a reproducible and noninvasive test of sympathetic function with a well-defined reflex pathway, 28 leading to an increase of muscle sympathetic nerve activity and plasma catecholamines. Isometrics also increase heart rate, cardiac output, left ventricular contractility, and systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%